CAK KISAH SENI MAGIS PERINTIS PERTUNJUKAN TURISTIK - Kadek Suartaya (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2004)
As a performing art form, Cak was designed as an aesthetical  presentation to be performed before an audience. It originated in the  village of Bedulu, a place also known for its traditional ritual dances,  Sanghyang Dedari and Sanghyang Jaran, for keeping away evil spirits.Artist (painter) WaIter Spies, who had the idea for this dance and the  dancer Baris I Wayang Limbak, who was the main creator and  performer. are the two people responsible for creating a performing art  work adopted from the sacred religious rituals mentioned above. The  excess of tourists which followed the journey of Cak in Bedulu led to  its development in the neighboring village of Bona, Gianyar.Although it has been adopted as a tourist perfo'rmance, the  tradition of performing Sanghyang in a religious context still continues  in the village of Bona. Therefore, Cak still exists as an  accompaniment to Sanghyang for various religious rituals, in particular  the dewa yadnya ceremony (offering a holy sacrifice to the gods) and  the buta yadnya ceremony (offering a holy sacrifice to the evil spirits)Key words: Cek, tourist performance, magic.